ANALISIS KINERJA MOTOR CIRCULATING WATER PUMP (CWP) UNIT 6 PT. PLN INDONESIA POWER UBP SURALAYA: Pendekatan Deskriptif Kuantitatif untuk Evaluasi Parameter Kelistrikan dan Mekanis Motor Tegangan Tinggi - FIANA, FIANA; Aribowo, Didik (Politeknik Caltex Riau, 2025)
This study aims to evaluate the performance of the Circulating Water Pump (CWP) Unit 6 motors at PLTU Suralaya using a quantitative descriptive approach based on operational data from the Supervisory Control and Data Acquisition (SCADA) system and the Distributed Control System (DCS). The assessment covers key electrical and mechanical parameters by referring to international standards, namely IEEE Std 112-2017 and IEC 60034-14. Data were collected during 24 hours of stable operation, resulting in 288 measurement points. The findings indicate that the CWP 6A and CWP 6B motors operated within safe limits, as shown by current values of 190 A and 192 A, stator temperatures ranging from 74–79 °C, and vibration levels below 0.1 mm/s, which are significantly lower than the allowable limit of 4.5 mm/s. These results confirm that both motors are in stable and efficient operating condition. Furthermore, the integration of SCADA–DCS proves to be effective in supporting predictive maintenance for high-voltage motor systems.